Conceptual basis of organization of volleyball team training - Bloshchynsky, I.; Kovalchuk, R.; Balendr, A.; Aloshyna, A.; Bahas, O.; Mozolev, O.; Prontenko, K.; Tomkiv, I.; Bychuk, O.; Prontenko, V. (International Journal of Applied Exercise Physiology, 2019)
The article investigates the issues of training of the sports team ("Novator" volleyball club) for competitions of the national championship and achieving high sports results. The basis of these studies is the analysis of the conceptual foundations of preparation of the sports team, the practical processing of results of the team's performance and establishing the relationship between the methods of the team's training, mental, emotional and physical activity of sportsmen. The purpose of the article is to study and summarize the practical experience of organization and functioning of a sports team from the moment of creation to the international arena; and to substantiate the conceptual basis for the preparation of a sports team to achieve high sports results in the future. The participants of the experiment were: 35 sportsmen and 7 participants of the trainer's staff of the sports team ("Novator" volleyball club, Khmelnytskyi). Methods. To achieve this goal the following set of methods were used: theoretical analysis, comparison, generalization, and systematization of theoretical and practical material, the study of the experience of coaches in order to justify the preparation of the volleyball team to the competitions of the national championship and achieve high sports results; formulation and systematization of conclusions. Conclusions. The article characterizes conceptual basis of preparing the team to compete at the national competition, which is based on three levels: theoretical, methodological and practical, that will allow in the future achieving high sports results in the international arena.